880MPa-grade low-anisotropy TC4ELI wide and thick plate and preparation method thereof
By adding C and Si elements to TC4ELI alloy sheets and optimizing the heating and rolling process, the problems of low longitudinal strength and large differences in the anisotropic properties of TC4ELI alloy sheets are solved, and a TC4ELI wide and thick plate with high strength and low anisotropy are achieved Preparation.
Patent Information
- Application Number
- CN202510031562.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing TC4ELI alloy sheets have problems with low longitudinal strength and large differences in anisotropic performance, which is difficult to meet the needs of high-strength scenarios.
By controlling the components of TC4ELI alloy, the appropriate amount of C elements and Si elements are added, and the grains are refined to reduce texture and anisotropy. By optimizing the heating method and rolling process, the transverse and longitudinal deformation ratios are controlled to reduce the rolling Anisotropy.
The overall yield strength and tensile strength of the 880MPa level of transverse and longitudinal direction are achieved, and the difference in transverse and longitudinal direction strength is controlled within 30MPa, solving the problems of low longitudinal strength and large differences in anisotropic performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TC4ELI alloy plates, and in particular to an 880MPa-grade low-anisotropy TC4ELI wide and thick plate and a preparation method thereof. Background Art
[0002] In TC4ELI alloy plates, the alloy strength is low due to the low content of interstitial elements (such as Fe, O, C, N and H). Specifically, the national standard "GB / T 3620.1-2016 Titanium and Titanium Alloy Grades and Chemical Compositions" strictly stipulates that the mass percentage range of TC4ELI alloy components is: Al: 5.5%-6.5%, V: 3.5%-4.5%, Fe<0.25%, O<0.13%, C<0.08%, N<0.03%, H<0.012%, other single impurity element content <0.1%, and the total content of other impurity elements <0.3%. Therefore, it is difficult to improve its strength performance by significantly adjusting the content of alloy elements.
[0003] For TC4ELI alloy plates with a thickness of more than 50 mm, the national standard "GB / T 3621-2022 Titanium and Titanium Alloy Plates" requires a transverse tensile strength R m ≥895MPa, R p0.2 ≥795MPa, and the longitudinal strength of the plate may be lower, which will cause the plate performance to fail to meet the use requirements of certain high-strength scenarios, and will also increase the transverse and longitudinal performance differences of the plate (i.e., isotropic performance differences). Specifically, during the rolling of titanium alloy plates, due to the large deformation in the longitudinal direction, the performance after rolling will show that the transverse strength of the plate is higher than the longitudinal strength, that is, anisotropy exists. In addition, due to the limitation of the rolling mill width, it is difficult to reduce the anisotropy of the plate by increasing the width ratio (i.e., the rolling ratio before and after the cross-rolling reversal).
[0004] In summary, it is necessary to develop an 880MPa-grade low anisotropy TC4ELI wide and thick plate and a preparation method thereof to solve the problems of low longitudinal strength and large difference in anisotropic properties of TC4ELI alloy plates in the prior art. Summary of the invention
[0005] The object of the present invention is to provide a 880MPa low anisotropy TC4ELI wide and thick plate and a preparation method thereof. The specific technical scheme is as follows: In a first aspect, the present invention provides a method for preparing a 880MPa low anisotropic TC4ELI wide and thick plate, comprising: Step S1, adding TC4ELI alloy components into a smelting furnace according to a required ratio to obtain a TC4ELI alloy ingot; the mass percentage ratio of the TC4ELI alloy components is as follows: 5.9% ~ 6.4%Al, 3.9% ~ 4.3%V, 0.17% ~ 0.20%Fe, 0.09% ~ 0.13%O, 0.03% ~0.05%C, 0.03% ~ 0.05%Si, the sum of other impurities is less than 0.1% and the balance is Ti; Step S2, forging the TC4ELI alloy ingot into a TC4ELI alloy slab; Step S3, after grinding and polishing the TC4ELI alloy slab, pure titanium plates are respectively bonded to the upper surface and the lower surface thereof to form a composite slab; Step S4: preheat the composite slab in a furnace at a temperature of 800 to 900°C for 6 to 8 hours; then, heat the composite slab to T β -70 ~ T β -20℃, keep warm for 1 - 2h; remove from oven; the T β is the β phase transition point temperature of the TC4ELI alloy ingot; Step S5, rolling the composite slab after being taken out of the furnace, controlling the ratio of the transverse deformation to the longitudinal deformation to be no greater than 1:4, to obtain a composite plate; Step S6: post-process the rolled composite plate to obtain a finished plate, namely, TC4ELI wide and thick plate.
[0006] Optionally, in step S2, the thickness of the TC4ELI alloy slab is 100 to 330 mm.
[0007] Optionally, in step S2, the process conditions used for forging include a six-fire forging process with a gradually decreasing temperature; the six-fire forging process includes two-fire forging at a temperature of 1080-1150°C, two-fire β-phase forging at a temperature of 1000-1050°C, and two-fire α+β forging at 920-960°C; wherein α+β forging means that at a temperature T β After heating at 20~50℃, forging is performed, that is, conventional two-phase zone forging, to obtain a dual-state structure or an equiaxed structure.
[0008] Optionally, in step S3, the pure titanium plate with a thickness of 1 to 1.5 mm is explosively bonded to the upper surface and the lower surface of the TC4ELI alloy slab.
[0009] Optionally, in step S5, transverse rolling is performed first, and then vertical reversal is performed for longitudinal rolling; during the transverse rolling, the transverse rolling ratio is controlled to be 10% to 50%; during the longitudinal rolling, the longitudinal rolling ratio is controlled to be 30% to 85%.
[0010] Optionally, in step S6, the post-processing includes straightening treatment and annealing treatment performed sequentially; the straightening temperature used in the straightening treatment is 450 ~ 600 ° C; the annealing temperature used in the annealing treatment is 700 ~ 800 ° C, and the annealing time is 2 ~ 4h.
[0011] Optionally, in step S6, the post-processing further includes grinding, trimming and surface polishing, which are sequentially arranged after the annealing; the grinding includes using a grinder to remove the oxide layer on the pure titanium plate and the TC4ELI alloy slab.
[0012] Optionally, in step S6, the thickness of the finished plate is not less than 50 mm.
[0013] Optionally, in step S6, the transverse and longitudinal overall yield strength R of the finished plate p0.2 >880MPa, tensile strength R m >990MPa, the difference in transverse and longitudinal strength is controlled within 30MPa.
[0014] In a second aspect, the present invention provides an 880 MPa-level low anisotropy TC4ELI wide and thick plate, which is prepared by the preparation method of the 880 MPa-level low anisotropy TC4ELI wide and thick plate.
[0015] The application of the technical solution of the present invention has at least the following beneficial effects: The present invention provides a 880MPa low anisotropic TC4ELI wide and thick plate and a preparation method thereof, which can prepare a lateral and longitudinal overall yield strength R p0.2 >880MPa, tensile strength R m The finished plate has a strength of >990MPa and a difference in transverse and longitudinal strength within 30MPa, which solves the problems of low longitudinal strength and large difference in anisotropic performance of TC4ELI alloy plates in the prior art. Specifically, in step S1 of the preparation method, the present invention controls the TC4ELI alloy composition and adds an appropriate amount of C and Si elements. On the one hand, grain refinement is conducive to weakening the texture and reducing anisotropy; on the other hand, the strength of the plate is improved by strengthening the grain refinement; at the same time, adding an appropriate amount of Si elements can increase the fluidity of the alloy and reduce the deformation resistance of the alloy during the hot working process; in step S4, by optimizing the heating method before rolling in step S5, the composite plate has a high surface temperature (T β -70 ~ Tβ -20℃, such as 950℃), the core temperature is slightly lower (such as 880℃); then, through step S5, rapid large deformation rolling is performed to increase the core temperature, so that the surface temperature and the core temperature are balanced during rolling; in step S5, the ratio of the transverse deformation to the longitudinal deformation is controlled to be no more than 1:4, so as to reduce the anisotropy after rolling, thereby reducing the difference in transverse and longitudinal performance of the finished plate. DETAILED DESCRIPTION
[0016] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0017] Embodiment 1: A method for preparing 880MPa low anisotropy TC4ELI wide and thick plate, comprising: Step S1, pressing the TC4ELI alloy components into electrodes according to the required proportions, and then smelting them in a VAR smelting furnace (i.e., vacuum consumable smelting furnace) to obtain a TC4ELI alloy ingot with a size of φ980*2750mm; the mass percentage proportions of the TC4ELI alloy components are as follows: 6.1%Al, 4.2%V, 0.18%Fe, 0.13%O, 0.04%C, 0.04%Si, the sum of other impurities is less than 0.1% and the balance is Ti; Step S2, forging the TC4ELI alloy ingot into a TC4ELI alloy slab with a size of 330 mm in thickness × 1600 mm in width × 3150 mm in length through six fires; the process conditions adopted for the forging include a six-fire forging process with a temperature gradually decreasing; the six-fire forging process includes two-fire forging at a temperature of 1080-1150°C (such as 1100°C), two-fire β-phase forging at a temperature of 1000-1050°C (such as 1020°C), and two-fire α+β forging at 928-958°C (such as 940°C); wherein α+β forging means forging at a temperature of T β After heating at 20 ~ 50℃, forging is performed, i.e. conventional two-phase zone forging, to obtain a dual-state structure or an equiaxed structure; Step S3, after grinding and polishing the TC4ELI alloy slab, a pure titanium plate is respectively bonded on the upper surface and the lower surface thereof by explosion method to form a composite slab; the pure titanium plate is a TA1 titanium plate, and the size specification is 1.5 mm in thickness × 1600 mm in width × 3150 mm in length; the pure titanium plate is used to control the surface oxidation of the TC4ELI alloy slab and reduce the risk of rolling cracking after the surface of the TC4ELI alloy slab is cooled; Step S4: preheat the composite slab in an electric heating furnace at a temperature of 800°C for 8 hours; then, heat the composite slab to T β -43℃ (i.e. 935℃), keep warm for 2h; take out of the oven; the T β is the β phase transition temperature of the TC4ELI alloy ingot, which is 978°C; Step S5, rolling the composite slab after being taken out of the furnace without dephosphorization, controlling the ratio of the transverse deformation to the longitudinal deformation to be no more than 1:4, to obtain a composite plate; specifically, when the composite slab starts rolling, the surface temperature of the composite slab is measured by an infrared thermometer to be 915°C, and the rolling process table is shown in Table 1. After the fifth rolling pass is completed, the sixth pass is vertically reversed, and the final rolling temperature is measured by an infrared thermometer to be 850°C. The ratio of rolling deformation before and after reversing is 1:2.5 (30.5%:77.5%) (i.e., 231.5 mm thickness reversing, the rolling ratio before reversing is (333-231.5) / 333, and the rolling ratio after reversing is (231.5-52) / 231.5); Step S6: The rolled composite plate is post-processed to obtain a finished plate, namely, a TC4ELI wide and thick plate, and the size of the finished plate is 51 mm in thickness×2100 mm in width×14000 mm in length.
[0018] In step S6, the post-treatment includes straightening treatment and annealing treatment performed in sequence; the straightening temperature used in the straightening treatment is 450°C, and then the composite plate is air-cooled to room temperature on a cooling bed to obtain a titanium alloy straightened plate; the annealing temperature used in the annealing treatment is 750°C, the annealing time is 3h, and the annealing is performed by entering the furnace (specifically a roller furnace) at a temperature, and air-cooling is performed after exiting the furnace.
[0019] In step S6, the post-processing also includes grinding, trimming and surface polishing, which are sequentially arranged after the annealing treatment; the grinding includes using a grinder to remove the oxide layer on the pure titanium plate and the TC4ELI alloy slab; the trimming is used to cut off the unevenly elongated parts of the head and tail and both sides of the long side of the TC4ELI alloy slab.
[0020] Table 1 Rolling parameters used in the rolling process of step S5 in Example 1
[0021] Embodiment 2: The difference from Example 1 is that in step S1, the mass percentage ratio of the TC4ELI alloy components is as follows: 6.4%Al, 4.3%V, 0.20%Fe, 0.10%O, 0.03%C, 0.03%Si, the sum of other impurities is less than 0.1% and the balance is Ti; T β 970℃; In step S2, the size of the TC4ELI alloy slab is 325 mm thick × 1600 mm wide × 2700 mm long; In step S3, the size of the pure titanium plate is 1 mm in thickness×1600 mm in width×2700 mm in length; In step S4, the composite slab is preheated in an electric heating furnace and then heated to T β -40℃ (i.e. 930℃); In step S5, when the composite slab starts rolling, the surface temperature of the composite slab is measured by an infrared thermometer to be 908°C, and the rolling process table is shown in Table 2. After the fifth rolling pass is completed, the sixth pass is vertically reversed, and the final rolling temperature is measured by an infrared thermometer to be 855°C. The ratio of rolling deformation before and after reversing is 1:2.1 (36.5%:75.5%) (i.e., 207.6 mm thickness reversing, the rolling ratio before reversing is (327-207.6) / 327, and the rolling ratio after reversing is (207.6-50.8) / 207.6); In step S6, the finished plate has a size of 50 mm in thickness×2500 mm in width×11000 mm in length.
[0022] In step S6, the straightening temperature used in the straightening process is 500°C.
[0023] Table 2 Rolling parameters used in the rolling process of step S5 in Example 2
[0024] Embodiment 3: Different from Example 2, in step S1, the mass percentage of the TC4ELI alloy components is as follows: 5.9% Al, 3.9% V, 0.17% Fe, 0.13% O, 0.05% C, 0.05% Si, the sum of other impurities is less than 0.1% and the balance is Ti; β It is 982℃.
[0025] Embodiment 4: Different from Example 3, the thickness of the slab after coating with pure titanium plate is 325 mm. In step S5, the ratio of rolling deformation before and after reversing is 1:4 (20%:80%) (i.e., for 260 mm thickness reversal, the rolling ratio before reversing is (325-260) / 325, and the rolling ratio after reversing is (260-52) / 260).
[0026] Comparative Example 1: Different from Example 1, in step S1, Si and C elements are not added to the TC4ELI alloy composition, and the mass percentage ratios used are as follows: 6.2%Al, 4.0%V, 0.18%Fe, 0.10%O, the sum of other impurities is less than 0.1% and the balance is Ti; T β 975℃; No preheating is used in step S4; In step S5, the rolling deformation ratio before and after the reversal is controlled to be 1:4.
[0027] Comparative Example 2: Different from Example 1, in step S1, a low amount of Si element and C element are added to the TC4ELI alloy composition, and the mass percentage ratio thereof is as follows: 6.2%Al, 4.0%V, 0.18%Fe, 0.10%O, 0.02%C, 0.02%Si, the sum of other impurities is less than 0.1% and the balance is Ti; T β 976℃; In step S5, the rolling deformation ratio before and after the reversal is controlled to be 1:2.9.
[0028] Comparative Example 3: Different from Example 1, in step S1, excessive amounts of Si and C are added to the TC4ELI alloy composition, and the mass percentage ratios thereof are as follows: 6.2%Al, 4.0%V, 0.20%Fe, 0.13%O, 0.07%C, 0.06%Si, the sum of other impurities is less than 0.1% and the balance is Ti; T β 980℃; In step S5, the rolling deformation ratio before and after the reversal is controlled to be 1:5.
[0029] Comparative Example 4: Different from Example 1, in step S1, the mass percentage ratio of the TC4ELI alloy components is as follows: 5.9%Al, 3.9%V, 0.17%Fe, 0.13%O, 0.05%C, 0.05%Si, the sum of other impurities is less than 0.1% and the balance is Ti; T β982℃; In step S4, no preheating is used; the temperature is directly raised to 940°C and kept for 2 hours; In step S5, the rolling deformation ratio before and after the reversal is controlled to be 1:3.8.
[0030] The finished plates prepared in Examples 1-4 and Comparative Examples 1-4 were sampled in the middle of the width for tensile mechanical property testing. The testing method was carried out in accordance with the national standard "GB / T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method". The test results are shown in Table 3. p0.2 is the yield strength, R m is the tensile strength, A is the elongation after fracture, and Z is the cross-sectional shrinkage rate.
[0031] Table 3 Performance test of each finished board prepared in Examples 1-4 and Comparative Examples 1-4
[0032] From the data in Table 3, it can be seen that the present invention can prepare the overall yield strength R in the transverse and longitudinal directions by using Examples 1-4. p0.2 >880MPa, tensile strength R m The finished plate has a strength of >990MPa and the difference between the transverse and longitudinal strength is controlled within 30MPa, which solves the problems of low longitudinal strength and large difference in anisotropic properties of TC4ELI alloy plates in the prior art.
[0033] In Comparative Example 1, Si and C elements were not added, and the longitudinal yield strength R p0.2 and transverse yield strength R p0.2 Both are insufficient; Comparative Example 1 did not use 800°C preheating, which resulted in a significant increase in the core temperature of the composite slab during the rolling process. On the one hand, it increased the texture strength and made the transverse and longitudinal anisotropy large. On the other hand, the excessively high core temperature also prolonged the cooling time of the plate after rolling, resulting in slightly insufficient alloy strength.
[0034] The contents of Si and C added in Comparative Example 2 are both lower than the lower limit, which makes the alloy solid solution strength insufficient and leads to a longitudinal yield strength R p0.2 and transverse yield strength R p0.2 The strength is insufficient.
[0035] The transverse and longitudinal rolling ratio used in Comparative Example 3 exceeds the standard, which increases the texture strength and makes the transverse and longitudinal anisotropy large; in addition, the added Si element and C element content exceed the upper limit, which easily produces brittle phases of titanium silicon compounds (such as Ti5Si3 and Ti3Si, etc.) or / and brittle phases of titanium carbide (such as TiC, etc.) during smelting or heat treatment, seriously reducing the elongation of the material.
[0036] In Comparative Example 4, 800°C preheating was not used, which resulted in a serious increase in the core temperature of the composite slab during rolling. On the one hand, this increased the texture strength, resulting in large transverse and longitudinal anisotropy. On the other hand, the excessively high core temperature also prolonged the cooling time of the plate after rolling, resulting in slightly insufficient alloy strength.
[0037] The edges of the finished plates prepared in Examples 1-4 were sampled for tensile mechanical property testing. The testing was carried out in accordance with the national standard GB / T 228.1-2021 Metal Material Tensile Test Part 1: Room Temperature Test Method. The test results were combined with the corresponding middle sampling performance data in Table 3 to form Table 4.
[0038] Table 4 Performance test of the middle and edge samples of each finished plate prepared in Examples 1-4
[0039] From the data in Table 4, it can be seen that no matter whether the central sampling test or the edge sampling test is performed, the present invention can prepare the overall yield strength R in the transverse and longitudinal directions by using Examples 1-4. p0.2 >880MPa, tensile strength R m The finished plate has a strength of >990MPa and the difference in transverse and longitudinal strength is controlled within 30MPa.
[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing 880MPa low anisotropy TC4ELI wide and thick plate, characterized in that: include: Step S1, adding TC4ELI alloy components into a smelting furnace according to a required ratio to obtain a TC4ELI alloy ingot; the mass percentage ratio of the TC4ELI alloy components is as follows: 5.9% ~ 6.4%Al, 3.9% ~ 4.3%V, 0.17% ~ 0.20%Fe, 0.09% ~ 0.13%O, 0.03% ~ 0.05%C, 0.03% ~ 0.05%Si, the sum of other impurities is less than 0.1% and the balance is Ti; Step S2, forging the TC4ELI alloy ingot into a TC4ELI alloy slab; Step S3, after grinding and polishing the TC4ELI alloy slab, pure titanium plates are respectively bonded to the upper surface and the lower surface thereof to form a composite slab; Step S4: preheat the composite slab in a furnace at a temperature of 800 to 900°C for 6 to 8 hours; then, heat the composite slab to T β -70 ~ T β -20℃, keep warm for 1 - 2h; remove from oven; the T β is the β phase transition point temperature of the TC4ELI alloy ingot; Step S5, rolling the composite slab after being taken out of the furnace, controlling the ratio of the transverse deformation to the longitudinal deformation to be no greater than 1:4, to obtain a composite plate; Step S6: post-process the rolled composite plate to obtain a finished plate, namely, TC4ELI wide and thick plate.
2. The method for preparing the 880MPa low anisotropy TC4ELI wide and thick plate according to claim 1, characterized in that: In step S2, the thickness of the TC4ELI alloy slab is 100 to 330 mm.
3. The method for preparing the 880MPa low anisotropy TC4ELI wide and thick plate according to claim 1, characterized in that: In step S2, the process conditions used for forging include a six-fire forging process with a gradually decreasing temperature; the six-fire forging process includes two-fire forging at a temperature of 1080-1150°C, two-fire β-phase forging at a temperature of 1000-1050°C, and two-fire α+β forging at 920-960°C; wherein β-phase forging means forging at a temperature of T β After the above heating, forging is performed. α+β forging means that at temperature T β After heating at 20 ~ 50℃, forging is performed.
4. The method for preparing the 880MPa low anisotropy TC4ELI wide and thick plate according to claim 1, characterized in that: In step S3, the pure titanium plates with a thickness of 1 to 1.5 mm are bonded to the upper and lower surfaces of the TC4ELI alloy slab by explosion.
5. The method for preparing the 880MPa low anisotropy TC4ELI wide and thick plate according to claim 1, characterized in that: In step S5, transverse rolling is performed first, and then vertical reversal is performed for longitudinal rolling; during the transverse rolling, the transverse rolling ratio is controlled to be 10% to 50%; during the longitudinal rolling, the longitudinal rolling ratio is controlled to be 30% to 85%.
6. The method for preparing 880MPa low anisotropy TC4ELI wide and thick plates according to claim 1, characterized in that: In step S6, the post-treatment includes a straightening treatment and an annealing treatment performed in sequence; the straightening treatment adopts a straightening temperature of 450 to 600° C.; the annealing treatment adopts an annealing temperature of 700 to 800° C. and an annealing time of 2 to 4 hours.
7. The method for preparing 880MPa low anisotropy TC4ELI wide and thick plates according to claim 6, characterized in that: In step S6, the post-treatment further includes grinding treatment, edge trimming treatment and surface polishing treatment sequentially arranged after the annealing treatment; the grinding treatment includes using a grinder to remove the oxide layer on the pure titanium plate and the TC4ELI alloy slab.
8. The method for preparing 880MPa low anisotropy TC4ELI wide and thick plates according to claim 1, characterized in that: In step S6, the thickness of the finished plate is not less than 50 mm.
9. The method for preparing 880MPa low anisotropy TC4ELI wide and thick plates according to claim 1, characterized in that: In step S6, the transverse and longitudinal overall yield strength R of the finished plate p0.2 >880MPa, tensile strength R m >990MPa, the difference in transverse and longitudinal strength is controlled within 30MPa.
10. A 880MPa low anisotropy TC4ELI wide and thick plate, characterized in that: The plate is prepared by the method for preparing 880MPa-grade low anisotropy TC4ELI wide and thick plate as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of TC4 wide and thick plate with excellent comprehensive performance
CN109266986A
Rolling method of TC4ELI titanium alloy large-width thick plate
CN109590330A
Method for preparing titanium alloy wide and thick plate through steel mill rolling mill
CN110695085A
Preparation method of TC4ELI titanium alloy wire of medical ultrasonic knife
CN116765163A
Manufacturing method of low-anisotropy titanium alloy plate
CN117418083A